Migration and employment in Tajikistan: Evidence from twelve districts in Khatlon Province, 2015 - 2023 - Lambrecht, Isabel B.; Akramov, Kamiljon T.; Aliev, Jovidon; Mardonova Tolibkhonovna, Mohru (International Food Policy Research Institute, 2024)
Tajikistan’s economy is highly dependent on personal remittances (World Bank, 2023). Lack of formal well-paid jobs and of private business opportunities locally to earn sufficient household income has motivated people to migrate abroad since the beginning of the 2000s (Shimizutani and Yamada, 2023; World Bank, 2023). Since 2006, the value of personal remittances was more than 25 percent of the country’s GDP, and by 2022, remittances were an estimated 51 percent of Tajikistan’s GDP (World Bank, 2022; Figure 1). Remittances are thus key to poverty reduction in Tajikistan (World Bank, 2023), yet such large reliance on remittances, while providing major opportunities for households to exit poverty, also poses significant vulnerability to reenter poverty and food insecurity in case of any negative shocks affecting employment at the migration location.